Introducing flexible retirement: A dynamic model - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
Typically economists arguing for flexible (or variable) retirement age, but they rely on steady state analysis. In this paper we consider the replacement of a mandatory retirement system with a flexible one in real time. We show that even if early retirement is duly punished, diminishing the effective retirement age by 1 year raises the first year's and the total expenditures during transition by 8% and 70% of the original annual expenditure, respectively.
Keywords: H11; H55; 330; retirement age; flexible retirement age; variable retirement age; transition cost